Reduced Gene Dosage of Tfap2c Impairs Trophoblast Lineage Differentiation and Alters Maternal Blood Spaces in the Mouse Placenta. Issue 2 (1st August 2015) - Kaiser, Stephanie; Koch, Yvonne; Kühnel, Elisabeth; Sharma, Neha; Gellhaus, Alexandra; Kuckenberg, Peter; Schorle, Hubert; Winterhager, Elke
Abstract: Tfap2c is required for placental development and trophoblast stem cell maintenance. Deletion of Tfap2c results in early embryonic loss because of failure in placental development. We evaluated the effect of reduced Tfap2c expression on fetal outcome and placental development. Sixty percent of the heterozygous mice were lost directly after birth. Labyrinthine differentiation was impaired, as indicated by enhanced proliferation and inclusions of cobblestone-shaped cell clusters characterized by expression of Tfap2c and glycogen stores. Moreover, expression of marker genes such as Cdx2, Eomes, Gata3, and Ascl2 are decreased in the spongiotrophoblast and indicate a lowered stem cell potential. On Day 18.5 postcoitum, the labyrinth layer of Tfap2c +/− placentas exhibited massive hemorrhages in the maternal blood spaces; these hemorrhages might have contributed to the significantly reduced number of live-born pups. These morphological alterations were accompanied by a shift toward sinusoidal trophoblast giant cells as the cell subpopulation lining the maternal sinusoids and toward reduction in expression of the prolactin gene family member Prl2c2, a finding characteristic of the spiral arteries lining trophoblast cells. The trophoblast stem cells heterozygous for Tfap2c exhibited a reduction in the expression level of stem cell markers and in their proliferation and differentiation capacity but did not exhibit changes in marker genes of the trophoblast giant cell lineage. Taken together, these findings indicate that a reduction in the gene dosage of placental Tfap2c leads to morphological changes in the labyrinth at midgestation and in the maternal blood spaces during late pregnancy.